2013
DOI: 10.1371/journal.pone.0052875
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiling of Human Dendritic Cell Populations and Models - Unique Profiles of In Vitro Dendritic Cells and Implications on Functionality and Applicability

Abstract: BackgroundDendritic cells (DCs) comprise heterogeneous populations of cells, which act as central orchestrators of the immune response. Applicability of primary DCs is restricted due to their scarcity and therefore DC models are commonly employed in DC-based immunotherapy strategies and in vitro tests assessing DC function. However, the interrelationship between the individual in vitro DC models and their relative resemblance to specific primary DC populations remain elusive.ObjectiveTo describe and assess fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
79
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 73 publications
5
79
1
Order By: Relevance
“…We now show that in oral mucosa, in contrast to skin, maturing of GE-LC, in addition to becoming CD1a -, became mRNA CD83 + . This is in line with our previous findings and those of others who reported HLA-DR + DC subsets in human tonsils that lack CD1a expression (Summers et al, 2001;Lundberg et al, 2013), indicating that migration to the draining lymph nodes cannot be ruled out. Most likely the loss of CD1a upon migration is caused by differences in the LP in GE vs. dermis in the SE, consistent with our previous observations that the phenotype of migrating DC is highly plastic and dependent on the cytokine balance in the tissue microenvironment (de Gruijl et al, 2006;Ouwehand et al, 2011a).…”
Section: Discussionsupporting
confidence: 93%
“…We now show that in oral mucosa, in contrast to skin, maturing of GE-LC, in addition to becoming CD1a -, became mRNA CD83 + . This is in line with our previous findings and those of others who reported HLA-DR + DC subsets in human tonsils that lack CD1a expression (Summers et al, 2001;Lundberg et al, 2013), indicating that migration to the draining lymph nodes cannot be ruled out. Most likely the loss of CD1a upon migration is caused by differences in the LP in GE vs. dermis in the SE, consistent with our previous observations that the phenotype of migrating DC is highly plastic and dependent on the cytokine balance in the tissue microenvironment (de Gruijl et al, 2006;Ouwehand et al, 2011a).…”
Section: Discussionsupporting
confidence: 93%
“…44 Thus, although the transcriptional profile of in vitro-generated MDDCs is more related to that of CD1c 1 blood DCs than to other primary DC populations, 46 the gene expression signature of MDDCs is also considerably skewed by IL-4 and, interestingly, it reveals a significantly higher expression of the prototypical AhR-target gene CYP1B1 than other in vitrogenerated DC populations. 46 Therefore, it is conceivable that differentiation-driving cytokines might determine the level of expression or activation of AhR in CD1c 1 DCs and MDDCs, thus explaining the cell-context dependency of the ERK-AhR link that we have observed.…”
Section: Il-4 Vs Flt3mentioning
confidence: 99%
“…Only MoDC (27) and Langerhans cells (LC) (28) have been generated reproducibly in vitro by many teams. Gene expression profiling and/or ontogenic studies showed that MoDC, Langerhans cell, and DC lines strikingly differ from LT-DC subsets and are more similar to monocytes or macrophages (4,(29)(30)(31)(32). Cultures of CD34 + progenitors with FLT3-ligand (FLT3-L) or thrombopoietin (TPO) have been reported to yield pDC, CD141 + CLEC9A + DC, or CD1c + DC (11,33,34).…”
mentioning
confidence: 99%